Metricfy: Aplikasi Pembelajaran Numerasi berbasis Web - Tanjung, Firda Rosiana; Widodo, Suprih (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
The low numeracy literacy among students is primarily due to two factors: a lack of interest in numeracy learning and limited learning resources. The Ministry of Education and Culture's National Assessment Programme in 2022 revealed that numeracy skills in Indonesia remain low, with only about 40,63% of students demonstrating numeracy competence. Improvement is necessary to achieve better results. The aim of this research is to develop an interactive numeracy application for student learning and assess its suitability. Development utilised Rapid Application Development (RAD) with three main phases: requirement planning, design, and implementation. Data collection involved surveys and quantitative descriptive analysis. In the final development phase, the application underwent testing to ensure functionality and effectiveness. Functional testing using black box methods showed all features performed as expected. Additionally, a System Usability Scale (SUS) survey administered to students yielded a score of 78.05, categorised as "acceptable" (good), indicating the application meets usability and effectiveness standards.